The signaling network that silences the spindle assembly checkpoint upon the establishment of chromosome bipolar attachment - Jin, Fengzhi (National Academy of Sciences, 2013)
Improper kinetochore attachments activate the spindle assembly checkpoint (SAC) to prevent anaphase onset, but it is poorly understood how this checkpoint is silenced to allow anaphase onset. Chromosome bipolar attachment applies tension on sister kinetochores, and the lack of tension delays anaphase onset. In budding yeast, the delay induced by tension defects depends on the intact SAC as well as increase in ploidy (Ipl1)/Aurora kinase and a centromere-associated protein ShuGOshin (Sgo1). Here we provide evidence indicating that Ipl1-dependent phosphorylation of the kinetochore protein Duo1 and Mps1 interacting (Dam1) prevents SAC silencing when tension is absent. The nonphosphorylatable dam1 mutant cells, as well as sgo1 mutant cells, are competent in SAC activation but unable to prevent SAC silencing in response to tension defects. We further found that phosphomimetic dam1 mutants exhibited delayed anaphase onset mainly due to the failure in SAC silencing, but destabilized kinetochore attachment likely plays a minor role in this delay. Because the tension resulting from bipolar attachment triggers the dephosphorylation of Dam1 by protein phosphatase 1, this dephosphorylation likely coordinates SAC silencing with chromosome bipolar attachment. Therefore, Sgo1, Ipl1 kinase, Dam1, and protein phosphatase 1 comprise the SAC silencing network that ensures the correct timing for anaphase onset.